Exploring Quaker Organising to Consider the Possibilities for Relational Leadership. Issue 2 (December 2019) - Allen, Stephen
Abstract : This paper develops the perspective of 'relational leadership' by exploring dynamics of influence within Quaker organising. The theory of relational leadership is drawn upon as it is connected with more sustainable and equitable ways of organising. A Quaker context is studied as it is conducive for understanding possibilities for relational leadership because there is no formal hierarchy. By applying three aspects of a relational leadership perspective (mutual influence process [1], momentary [2] and socially co-constructed [3]) to a thematic analysis of interview data, understanding is developed about the potential dynamics of influence and leadership in non-hierarchical organising. Two contributions to relational leadership theory are offered. Firstly, the paper shows a need for greater critical attention to appreciate the potential subtleties and tensions involved in influencing dynamics in non-hierarchical organising; and, secondly, assumptions about the continuous potential for fluidity of influencing are challenged.